Conjoined ultra‐wideband (2, 300‐6, 000 MHz) dual antennas for LTE HB/WiFi/5G multi‐input multi‐output operation in the fifth‐generation tablet device. Issue 8 (19th February 2019) - Wong, Kin‐Lu; Chen, Yu‐Han; Li, Wei‐Yu
Abstract: Conjoined dual antennas with an ultra‐wideband (UWB) of 2300‐6000 MHz for multi‐input multi‐output operation in the fifth‐generation (5G) tablet device is presented. The UWB covers not only the 5G band in 3300‐5000 MHz, but also the long term evolution high band in 2300‐2400/2500‐2690 MHz and the Wireless Fidelity band in 2400‐2500/5100‐5900 MHz. Additionally, the envelope correlation coefficient in the UWB is less than 0.1. The conjoined dual antennas have a planar printed structure and require only 32.2 mm (about 0.25‐wavelength at 2.3 GHz) along the edge of the device ground plane. The dual antennas share a conjoined section of a ring strip for bandwidth enhancement and a band‐pass resonant structure for effective decoupling. The band‐pass resonant structure is formed by a printed structure of distributed capacitor and inductor connected in series. Details of the conjoined UWB dual antennas are presented.